Analisis Sistem Pengelolaan Keuangan Desa Melalui Penerapan Siskeudes Terhadap Kualitas Akuntabilitas Keuangan Desa di Kantor Desa Ciherang Kecamatan Banjarsari Kabupaten Ciamis - Candra Setiawan; Nana Darna (Master Manajemen, 2023)
Ciherang Village is one of the villages in Banjarsari District, Ciamis Regency that implements an information technology-based financial management system, namely Siskeudes. The Siskeudes application itself is a tool intended for the Village Government in Village Financial Management starting from the planning, implementation, administration, reporting, and accountability stages in a computerized manner. The purpose of using this Siskeudes application system is to improve the quality of accountability in village financial management. This is in accordance with what is stated in the law regarding financial management which contains various activities starting from planning, implementation, administration, reporting, and accountability. This type of research is an explanatory survey. The selection of this method is based on the consideration that this method not only explains or describes empirical facts in the field, but will also explain the analysis of influence. The method is a research method that highlights the relationship or influence between research variables by testing previously formulated hypotheses. The location of the research is in Ciherang Village, Banjarsari District, Ciamis Regency. The population of this study is village officials who are members of the village government headed by a village head using census techniques. Based on the description of the research results and discussions that have been carried out, the researcher can conclude that the financial management system in the Ciherang Village Government is considered quite good. This can be seen from the implementation of management that is in accordance with existing regulations, although it still needs to be improved, especially in terms of community participation and discipline applied to village officials in the Ciherang Village Government.